2021
DOI: 10.3390/w13060806
|View full text |Cite
|
Sign up to set email alerts
|

Variations of Groundwater Dynamics in Alluvial Aquifers with Reclaimed Water Restoring the Overlying River, Beijing, China

Abstract: Some of the rivers in northern China are dried, and reclaimed water (RW) is used to restore these degraded river ecosystems, during which the RW could recharge the aquifer by river bank infiltration. From 2007 to 2018, 2.78 × 108 m3 of RW has been replenished to the dried Chaobai River (Shunyi reach), Beijing, China, which is located on the edge of one depression cone in groundwater caused by groundwater over-pumping. The groundwater hydrodynamic variations and the flow path of the RW were identified by eight-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…Besides RW, industrial pollution in the study area is also the source of Cl − inputting into groundwater. But the latter didn't affect the uncon ned groundwater surrounding the monitoring wells except G32 (He et al, 2021). The high Cl − concentrations in the uncon ned groundwater along the river are mainly affected by the RW in ltration.…”
Section: Data Sourcesmentioning
confidence: 94%
See 3 more Smart Citations
“…Besides RW, industrial pollution in the study area is also the source of Cl − inputting into groundwater. But the latter didn't affect the uncon ned groundwater surrounding the monitoring wells except G32 (He et al, 2021). The high Cl − concentrations in the uncon ned groundwater along the river are mainly affected by the RW in ltration.…”
Section: Data Sourcesmentioning
confidence: 94%
“…Many studies have been carried out on characterizing variations in physical and chemical parameters of groundwater after RW recharge in the study area, with the most signi cant changes in the uncon ned aquifer. The groundwater table increased by ~3 m after RW supply to the Chaobai River from 2007 to 2018 (He et al, 2021). Column experimental results indicated that cation exchange took place between K + in the RW and Ca 2+ in the riverbed medium during RW in ltration (Liu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, owing to excessive exploitation, groundwater resources were over-consumed, resulting in a sharp drop in groundwater levels in some regions. To alleviate the groundwater crisis, managed aquifer recharge, an intentional measure of anthropogenic groundwater recharge (AGR), is usually applied along rivers, infiltration basins, or lakes, where clean surface water can easily infiltrate into highly permeable shallow aquifers, thereby increasing groundwater resources. , However, contaminants from the surface and vadose zone can be introduced into the aquifer through AGR, resulting in groundwater pollution . In addition, since there are differences in water quality between recharge surface water and natural groundwater, AGR can change water-rock interactions to degrade groundwater quality. , For example, many studies have reported that AGR can result in nitrate pollution. , Thus, the groundwater quality risks and regional applicability of AGR remain to be explored. , …”
Section: Introductionmentioning
confidence: 99%